ASSESSMENT OF CHROMATOGRAPHIC SEPARATIONS FOR ANTIHYPERTENSIVE AND ANTIDIABETIC DRUGS - Venkataraman, Sowmyalakshmi; G, Haritha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Context: The focus of this review is to compile the different chromatographic methods that were reported earlier for the analysis of different antihypertensive and antidiabetic drugs. Objective: The magnitude of chemical entities investigated and entering into the medicinal field for various health-related ailments is escalating year after year. The drugs are either innovative entities or fractional structural variation of the preexisting chemical molecule. These drugs may exhibit unexpected toxicities after Phase IV of clinical trials, resulting in their withdrawal from the market. Under these circumstances, analytical measures for these drugs may not be accessible in the pharmacopeias. The main aim of this work is to compile the different analytical techniques for the quantification of various antihypertensive drugs and antidiabetic drugs. Methods: The present work is to thoroughly study the literature for the application of different analytical techniques such as high-performance liquid chromatography (HPLC) and liquid chromatography-mass spectroscopy/tandem mass spectroscopy (LC-MS/MS) for the quantification of antihypertensive drugs and anti-diabetic drugs. Results: The present study attempts to collate various analytical techniques that were developed and validated for the estimation of few important antidiabetic and antihypertensive drugs either in pure, individually or combined with other pharmaceutical dosage form by HPLC, LC-MS/MS, and high-performance thin-layer chromatography techniques. Conclusion: Different chromatographic methods are considered to be rapid tools for qualitative and quantitative analysis of newer chemical entities in pharmaceuticals. The amount of these newer chemical entities which are reaching the pharmaceutical market is increasing day by day nevertheless there exists a lag in establishing the standard protocols for the identification, impurity profiling, related substance and assay method. Hence, the present review compiles the different analytical methods that were reported in the literature and thus helps the researchers and chemists to make use of the analytical techniques for the quantification and validation of various antidiabetic and antihypertensive drugs.